PERAN PENDIDIKAN KESETARAAN DALAM LINGKUNGAN MASYARAKAT - Nurhanipah; Arin Khairunnisa (Yayasan Nusantara Hasana Berdikari, 2023)
Equality education is a non-formal education channel facilitated by the Government/Society for students who study not through formal education (school route). In Equality Education, there are 3 packages, namely Pursue Packages A, B, and C Pursue Packages A, B, and C is a solution for those of us who have dropped out of school due to relatively low family economic conditions or are even over school age but want to have knowledge, abilities, and certificates equivalent to those of elementary, junior high, and high school. the purpose of this study was to determine the role of Equality Education in fostering school dropouts. Through this Equality Education program, students will receive equivalent lessons according to their level. This package of learning activities is carried out flexibly compared to formal schools, meaning that learning is not carried out in full in 1 week but is only carried out 3 times a week. Equality Education programs are essential to the attainment of basic education learning as well as meeting educational needs and ensuring that all members of society have equal access to education services.